Religiosity, money ethics, materialism, and tax evasion: An exploratory study - Jannah, Nur (JIFA (Journal of Islamic Finance and Accounting), 2023)
Tax evasion remains a persistent concern that continues to captivate the attention of scholars and professionals alike, owing to its profound implications for a nation's economic landscape. The objective of this study is to assess the impact of money ethics, intrinsic religiosity, and extrinsic religiosity on tax evasion. Specifically, the study aims to examine the moderating effects of intrinsic religiosity, extrinsic religiosity, gender, and materialism on the relationship between money ethics and tax evasion. A purposive sampling technique is employed to select participants for this study, and primary data is collected through the direct distribution of questionnaires to respondents. The sample size consists of 100 participants. Structural Equation Modeling-Partial Least Squares (SEM-PLS) is utilized as the data analysis technique. The findings of the analysis reveal that money ethics and extrinsic religiosity positively influence tax evasion, while intrinsic religiosity has a negative impact on tax evasion. Moreover, the moderating effect of intrinsic religiosity weakens the relationship between money ethics and tax evasion, whereas the moderating variables of extrinsic religiosity, gender, and materialism do not demonstrate significant effects on the relationship between money ethics and tax evasion. This research provides practical contributions to the government in understanding the reasons behind taxpayers' behavior in engaging in tax evasion.